Some interesting lichens on volcanic rocks in the inland regions of the Iberian Peninsula - Gregorio Aragón; Gil Fernando Giménez; Valerie Negrón (Anales del Jardín Botánico de Madrid)
We report the first record of Acarospora insolata, A. irregularis, Caloplaca interna, Endocarpon adsurgens, and Flavoplaca limonia in the Iberian Peninsula. The species inhabit volcanic rocks in the Spanish Central Volcanic Region. This finding represents a significant expansion of the distribution range of these five species.